Inovasi Tata Letak Fasilitas pada Divisi Produksi PT. XYZ sebagai Solusi untuk Mengoptimalkan Proses Bisnis - Bagas Swardhana Putra; Magister Alfatah Kalijaga (Jurnal Studi Inovasi, 2021)
Facility layout design is an activity that consists of the design process, concept formation, and analysis of physical facilities including equipment, machinery, areas, buildings, and other physical facilities to optimize the flow of materials, information, and work processes. PT. XYZ is a company that focuses on processing yarn to then be produced into semi-finished fabric or commonly called gray fabric. The problems that occur in PT. XYZ is a workflow arrangement that is still not good. In addition, there is also the use of the production area that is not optimal and results in the existing trajectory distance between work units and the process of moving goods becomes less efficient and causes a waste of time and costs. The approach that can be used to solve these problems is the Activity Relationship Chart (ARC) which is useful for connecting activities in pairs to determine the level of the relationship. The results showed that there were problems in the placement of raw material warehouses and storage warehouses that were located too far from the inside of the company, making it difficult for the process of moving raw materials and finished products. In addition, there are also other problems in the form of an alternating flow pattern in the production process which causes material handling to be ineffective and inefficient.